2004
DOI: 10.1084/jem.20031579
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Functional Suppression by CD4+CD25+ Regulatory T Cells in Patients with Multiple Sclerosis

Abstract: CD4+CD25+ regulatory T cells contribute to the maintenance of peripheral tolerance by active suppression because their deletion causes spontaneous autoimmune diseases in mice. Human CD4+ regulatory T cells expressing high levels of CD25 are suppressive in vitro and mimic the activity of murine CD4+CD25+ regulatory T cells. Multiple sclerosis (MS) is an inflammatory disease thought to be mediated by T cells recognizing myelin protein peptides. We hypothesized that altered functions of CD4+CD25hi regulatory T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

75
1,251
12
27

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,648 publications
(1,365 citation statements)
references
References 30 publications
75
1,251
12
27
Order By: Relevance
“…3B). These findings confirm recent observations by Viglietta et al [24], who tested T reg in a cohort of 15 MS patients using polyclonal stimulation with plate-bound anti-CD3 and found a consistently reduced suppressive effect mediated by CD4 + CD25 high T cells.…”
Section: T Reg Derived From Ms Patients Exhibit Reduced Suppressive Psupporting
confidence: 92%
See 2 more Smart Citations
“…3B). These findings confirm recent observations by Viglietta et al [24], who tested T reg in a cohort of 15 MS patients using polyclonal stimulation with plate-bound anti-CD3 and found a consistently reduced suppressive effect mediated by CD4 + CD25 high T cells.…”
Section: T Reg Derived From Ms Patients Exhibit Reduced Suppressive Psupporting
confidence: 92%
“…A similar subpopulation of CD4 + CD25 high T cells is present in human peripheral blood and lymphoid organs [6][7][8][9][10][11][12][13]. From a few recent studies, it appears that T reg numbers are reduced or their function is impaired in patients with various autoimmune disorders [17][18][19][20][21][22][23][24]. The impact of CD4 + CD25 high T cells in immunoregulation is critically supported by observations of Bennett et al [37] who demonstrated that mutations of Foxp3, a transcription factor which is essential for CD4 + CD25 high T cell function, cause the immune dysregulation, polyendocrinopathy, enteropathy, and X-linked syndrome (IPEX).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is of potentially important clinical value since T reg function is known to be impaired in patients with MS 1, 2, 3. Since suppressive function often corresponds to the production of IL‐10, we next determined if stimulation with PSA resulted in an increase in IL‐10 production.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the fluctuation between relapse and remission is greatly influenced by the balance of self‐reactive effector T cells and regulatory T cells (T regs ). Importantly, studies have shown that while MS patients harbor normal frequencies of T regs , their production of IL‐10 and overall suppressive capacity is significantly reduced allowing for increased inflammation driven by effector cells 1, 2, 3. For many years, the immunopathogenesis of this condition was attributed to an imbalance of Th1/Th2 polarization in which the enhanced Th1 response was associated with the production of IFN γ and TNF α .…”
Section: Introductionmentioning
confidence: 99%